Exploring the Relationship Between the Supervisory Alliance and the Development of Reflexive Self-Awareness: A Mixed Methods Approach - Alexandre Brien; Réginald Savard; Cynthia Bilodeau; Patricia Dionne (Teaching and Supervision in Counseling, 2023)
The study used embedded design to explore the relationship between alliance and perceived change in reflexive self-awareness in graduate trainees following counseling and psychotherapy programs (n = 48). Linear regression analyses were used to measure the predictive value of alliance on the development of supervisees' reflexive awareness. Qualitative reflexive thematic analysis was also conducted on critical incident reports of supervisees who perceived low vs strong alliances to gain greater in-depth understanding of the quantitative data. Results showed that the alliance does not directly predict observed changes in reflexive awareness. While alliance was found to create favorable conditions to support the development of reflexive self-awareness, it did not suffice to promote supervisees’ engagement in such development. Consequently, the results suggest it is important to consider difficulties in emotion regulation that may be inherent in the supervisory process to promote reflexive self-awareness in supervisees.
Keywords: Supervisory Alliance; Reflexive Self-Awareness; Trainees; Mixed Methods